Relationship Between Strategic Management Training and Firm Performance Among Small and Medium Enterprise Managers in South-East Nigeria - Anyakoha, Chukwunonye (Papanda Publisher, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in economic development, yet many struggle with poor performance due to inadequate strategic management capabilities. This study examines the relationship between strategic management training and firm performance among SME managers in South-East Nigeria. The objectives are to assess the extent of strategic management training received by SME managers in South-East Nigeria, evaluate the impact of strategic management training on the performance metrics of SMEs in South-East Nigeria and identify the challenges encountered by SME managers in applying strategic management principles after undergoing training. Te study adopted a correlation analysis while simple regression was used to test hypotheses. A quantitative research design was employed, utilizing a survey method. Data were collected from 300 SME managers using structured questionnaires. The instrument was validated through expert review and reliability was confirmed using Cronbach’s alpha. Descriptive and inferential statistics, including regression analysis, were used for data analysis. The findings reveal a significant positive relationship between strategic management training and firm performance, with improvements observed in growth, efficiency, and profitability. The study concludes that structured strategic management training enhances SME performance, recommending targeted training programs to improve managerial capabilities. Future research should explore sector-specific training impact Keywords: Strategic management training, firm performance, SMEs, South-East Nigeria, managerial capability.